OPTIMALISASI PENGGUNAAN PERANGKAT ATC SYSTEM (TERN) DALAM PELAYANAN ATS MESSAGES DI UNIT ATS-RO PERUM LPPNPI CABANG DENPASAR - Dwi Fitrianingsih; Abdul Mu’ti Sazali; Syahrul Aman (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
ATC System (Tern) in Perum LPPNPI Denpasar Branch is the third in Indonesia, the first is in Balikpapan, then Jogja and the third is Bali and Surabaya. TERN itself has complete features and superior but there are still problems in it caused by some things so it can not be perfect in service in the unit ATS Reporting Office (ARO) Denpasar. Some of the problems encountered are error handling, terminated which takes more time, some waypoint VFR route that has not been registered and some FPL that has not been accommodated properly. The purpose of this study is to find out if optimization of Tern device usage can support ATS Messages services in ARO units, to know how to optimize for better use of Tern devices in the future. In the work of this Final Task the author uses qualitative descriptive methods with observation and interview data collection techniques. For observation the author did so from December 2020 to March 2021. From the results of the research conducted, the authors found the results that ACO personnel think that Tern is very useful in terms of monitoring every existing flight data, namely Flight Plan, Delay, Change, Arrival, Departure, Cancel, etc. But there are also obstacles that some features in Tern are not optimal so as to make the ATS Messages service a little hampered or take more time. Due to constraints in some features, the use of TERN devices is less optimal because ACO personnel prefer to use WBF to make FPL changes. See from some research that the authors of the study about TERN all have in common that TERN is very useful for each unit whether it is APP / TMA, Tower or ARO because the features are very useful for these units.